EVALUATE THE EFFECTS OF CT-GUIDED SPLANCHNIC NERVE NEUROLYSIS IN PAIN CAUSED BY UPPER ABDOMINAL VISCERAL MALIGNANCIES - Tong , Ngoc Tien; Pham , Minh Thong; Nguyen , Thi Van; Ngo , Le Lam; Nguyen , Quoc Dat (Tạp chí Điện quang & Y học hạt nhân Việt Nam, 2023)
Objective: This study aims to assess the efficacy of CT-guided splanchnic nerve neurolysis in alleviating pain associated with malignancies in the upper abdominal viscera.Methods: A single-arm investigation involved 20 patients diagnosed with upper abdominal visceral malignancies and experiencing pain with a VAS ≥ 7. All participants underwent CT-guided splanchnic nerve neurolysis utilizing absolute alcohol ablation. Pain intensity was measured using the visual analog scale (VAS) one-day post-procedure, at one week, and at one-month follow-up. The primary endpoint was to evaluate the effectiveness of pain relief based on VAS scores. Incidences of intra- and post-procedural complications were meticulously documented.Results: The mean age of participants was 60.7±11.1, with 12 men and 8 women included in the study. Assessment of pain relief, as per the Visual Analogue Scale (VAS) one day following the intervention, revealed a 70% efficacy in the group with substantial relief and 30% with moderate relief. The average VAS score exhibited a significant decrease immediately post-intervention (8.7±1.1 vs. 3.4±1.3, p<0.05). The average VAS scores remained relatively stable at 2.6±1.5 and 2.1±1.5 at the one-week and one-month follow-up, respectively. Common complications included orthostatic hypotension (40%), initial pain (30%), acute intoxication (25%), and diarrhea (15%). No instances of severe complications were recorded.Conclusion: CT-guided splanchnic nerve neurolysis using absolute alcohol is deemed a secure and productive method for promptly mitigating pain and sustaining pain stability for up to one month.